Co-making the future: judges’ insights on transdisciplinary creativity and global collaboration in the China-U.S. young maker competition - Liu, Wei; Zhu, Yancong; Li, Yin; Fu, Zhiyong; Sun, Yuanbo; Hong, Xinhui; Li, Yanru; Liu, Min (Frontiers in Education, 2024)
This paper examines the future of maker education through an analysis of feedback from judges in the China-U.S. Young Maker Competition. Drawing on inputs from 36 judges from diverse backgrounds in academia, industry, and sponsoring companies, the study uses thematic analysis of interviews, feedback, and focus group discussions to uncover key educational trends. It highlights critical themes such as transdisciplinary creativity, real-world application, sustainability, cross-cultural collaboration, and innovation mindset. The research reveals a trend towards integrating various academic fields to boost creative problem-solving and application in real-life scenarios. Sustainability is identified as a crucial component, pointing to the need for environmentally aware education. The study also emphasizes the importance of cross-cultural collaboration for global interconnectedness and adaptive problem-solving, alongside fostering a continuous innovation mindset in students. Concluding with future directions for maker education, the paper advocates for an experiential, inclusive, and forward-looking educational approach. It underscores the importance of a broad curriculum that integrates entrepreneurial skills, promotes lifelong learning, and enhances global connectivity. This study provides insights for educators, policymakers, and practitioners, offering a streamlined roadmap for advancing maker education in a rapidly evolving global context.